A Preliminary Investigation of the Contribution of Different Tenderness Factors to Beef Loin, Tri-tip, and Heel Tenderness - C. K. Chun; W. Wu; A. A. Welter; T. G. O'Quinn; G. Magnin-Bissel; D. L. Boyle; M. D. Chao (Kansas Agricultural Experiment Station Research Reports, 2021)
Objective:The objective is to better understand the contribution of each tenderness factor to the perception of tenderness of three specific beef muscles with similar tenderness ratings. Study Description:Longissimus lumborum (loin), tensor fascia latae (tri-tip), and gastrocnemius (heel) were collected from 10 U.S. Department of Agriculture low Choice beef carcasses and assigned to a 5- or 21-day aging period (n = 60). Steaks from each aging period from each subprimal were assigned to one of three assays: 1) trained sensory analysis; 2) objective tenderness evaluation (Warner-Bratzler shear force); or 3) physiochemical analysis (sarcomere length, proteolysis, intramuscular fat content, collagen crosslink, and content). Results:Sarcomere length, troponin-T degradation, collagen content, mature collagen crosslink density, intramuscular lipid content, and trained panel analysis were measured. Correlation analysis indicated each muscle has a specific tenderness factor that contributed to the overall tenderness evaluated by trained panelists. The equations indicated Longissimus lumborum tenderness was driven by lipid content (P<0.05) and that Tensor fascia latae tenderness was driven by collagen content (P<0.05). Gastrocnemius tenderness was driven by proteolysis (P<0.01), and only collagen content can be casually used as an overall tenderness predictor for all three cuts. The Bottom Line:Each muscle showed a unique tenderness factor profile. Loin is inherently tender, and tri-tip has the makings for a tender cut as seen by our biochemical analysis, yet panelists rated tri-tip to have similar overall tenderness as heel, an inherently tough muscle.
Keywords: beef; tenderness; collagen-crosslink